Penerapan Pendekatan Somatis Auditori Visual Intelektual Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS - Septyani, Natria; Hanifah, Nurdinah; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
The application of the SAVI approach aims as an action in the implementation of social studies learning to improve students’ critical thinking skills. This is due to the fact on the ground that students’ critical thinking skills are still very low, so it is necessary to take action to improve students’ critical thinking skills. The existence of the application of the SAVI approach as an action in the implementation of social studies learning to improve students’ critical thinking skills. This is because in the SAVI approach, student activties become more active by utilizing the student’s body movement abilities and intellectual abilities so that it can generate integrated intelligence that can improve the ability to analyze in critical thinking. This research is a level 3 action research by finding the initial potential of the low critical thinking ability of students in social studies learning and developing the action of applying the SAVI approach as an action in solving problems. Through the SAVI approach, it can be seen that there is an increase in the average value of students’ critical thinking skills from 73 to 81. Thus, the SAVI approach can be taken as an action to improve students’ critical thinking skills.